STABILISASI INFLOW PERFORMANCE PADA KONDISI TRANSIENT DENGAN METODE DIMENSIONLESS - Yolanda S Sagala, Theresia
This study presents the result of the Inflow Performance Relationship using transient data and pseudo steadystate data. Due to the large difference in results, transient data are considered less representative of IPR in stable conditions. So, an appropriate IPR calculation method using transient data was developed to approach the IPR result using pseudo steady-state data. Pressure in stable flow is obtained from transient data using dimensionless nonlinear regression equation of the stable time curve on the solution-gas drive reservoir. This calculation is combined with John Lee’s stabilized time equation (1982). This method is validated by comparing the IPR calculated using pseudo steady-state, transient, and stabilized data. From these three IPR curve, concluded that transient data gives much greater results than pseudo steadystate data. Diameter of the tubing installed in the well is larger as well as the flow rate obtained in the nodal analysis. Meanwhile the IPR calculated using stabilized data through dimensionless method succeeded in approaching the IPR in stable conditions. The result of this study is applicable for well testing that must be done in a short-period of time and has not reached pseudo steady-state condition. This method can be easily applied and well-used on porosity above 0.1 for giving more accurate calculation result. This study was conducted based on computer simulation results on a single value of viscosity, compressibility and drainage radius. So, additional cases with varying characteristic values and field data verification are required.